2022
DOI: 10.1136/gutjnl-2021-325811
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 1 (IRF1) controls the metabolic programmes of low-grade pancreatic cancer cells

Abstract: ObjectivePancreatic ductal adenocarcinomas (PDACs) include heterogeneous mixtures of low-grade cells forming pseudoglandular structures and compact nests of high-grade cells organised in non-glandular patterns. We previously reported that low-grade PDAC cells display high expression of interferon regulatory factor 1 (IRF1), a pivotal transcription factor of the interferon (IFN) system, suggesting grade-specific, cell-intrinsic activation of IFN responses. Here, we set out to determine the molecular bases and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 89 publications
1
10
0
Order By: Relevance
“…The Panc1005 cell line showed highest m5C-score, followed by CAPAN1, while PANC1 showed the lowest m5C-score (Figure 7H and Supplementary Table S8-7). In addition, the sequencing data from four pancreatic cancer cell lines (CAPAN1, PANC1, MIAPACA2 and CFPAC1) was acquired from GSE165949 (Alfarano et al, 2022). CAPAN1 showed the highest m5C-score, the PANC1 showed the lowest m5C-score, while MIAPACA2 cells had an almost negative m5C-score, confirming the results above (Figure 7G; Supplementary Table S8-8).…”
Section: Pdac Is Characterized By Frequent Overexpression Of Erbb Rec...supporting
confidence: 80%
See 1 more Smart Citation
“…The Panc1005 cell line showed highest m5C-score, followed by CAPAN1, while PANC1 showed the lowest m5C-score (Figure 7H and Supplementary Table S8-7). In addition, the sequencing data from four pancreatic cancer cell lines (CAPAN1, PANC1, MIAPACA2 and CFPAC1) was acquired from GSE165949 (Alfarano et al, 2022). CAPAN1 showed the highest m5C-score, the PANC1 showed the lowest m5C-score, while MIAPACA2 cells had an almost negative m5C-score, confirming the results above (Figure 7G; Supplementary Table S8-8).…”
Section: Pdac Is Characterized By Frequent Overexpression Of Erbb Rec...supporting
confidence: 80%
“…Patients without survival data were removed from further survival-related analyses. The cell line RNA-seq data were obtained from the Moffitt's cohort data (GSE71729) and GSE165949 (Alfarano et al, 2022), the latter as data normalized by "summarizeOverlaps" from the R package GenomicRanges (v. 1.38). Basic information of these datasets is listed in Supplementary Table S1, and the study workflow is presented in Supplementary Figure S1.…”
Section: Collection and Pre-processing Of Pancreatic Ductal Adenocarc...mentioning
confidence: 99%
“…2B ). Instead, MiaPaca2 cells contain a large deletion of the INK4/ARF locus that extends to the type I IFN gene cluster ( 45 ). However, in these cells, the type III IFN gene IFNL3 was induced in response to trametinib ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the role of ELF3 induction by trametinib in the transcriptional activation of retroelements and in the activation of the IFN response, we used ELF3-null CFPAC1 cells previously generated by genome editing in our laboratory ( 45 , 53 ). The lack of ELF3 globally and strongly attenuated induction of IFN-stimulated genes in response to trametinib ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…KLF5 was the most highly expressed TF in low-grade versus high-grade tumors, and despite its motif not showing enrichment in low-grade enhancers, the authors demonstrated that KLF5 is an important determinant of epithelial differentiation in low-grade tumor cell lines [53] . Unlike other TFs linked with the classical subtype, KLF5 knockout in mouse models completely abolished tumorigenesis, apparently by preventing acinar-to-ductal metaplasia, an essential first step in tumorigenesis initiated in acinar cells [10,55] .…”
Section: Tf Determinants Of Classical Pdamentioning
confidence: 96%